Determining the chlorine kinetic behavior in surface water using evolutionary metaheuristic algorithms - Farhad Mahmoudi Jalali; Seyyed Roohollah Masoomi; Mostafa Azizi; Reza Aghlmand; Mohammad Gheibi; Zahra Kian (Annals of Systems Biology - Peertechz Publications, 2021)
The use of a reliable technique in measuring the residual chlorine concentration is of particular importance. Because based on the results of these measurements, the water quality of the network is calculated and evaluated in terms of ensuring the health of the community. The concentration of residual chlorine in the effluent of the treatment plant decreases as water flows through the distribution network. Chlorine decay is divided into two categories: wall and mass decay. Various detectors such as DPD and Ortho-toluidine can be used to measure residual chlorine. This study is the first step in the spectroscopy of chlorine and Ortho-toluidine color complex. The results of this stage of the research indicate that to measure the residual chlorine concentrations, the absorbed values should be read at a peak of 450 nm. In the next step, after measuring the free chlorine concentrations remaining at different times, the degree of chemical reaction was determined using multivariate nonlinear regression methods. In the final step, the reaction coefficient was calculated by simulating the differential equation in the Simulink environment and optimizing the error of the initial values of the reaction constant to the real values using the genetic algorithm (GA). The results of the analysis showed; The mass decay of chlorine in the sample follows the quadratic and the reaction constant is equal to 0.005 .